Stellar feedback from high-mass X-ray binaries in cosmological hydrodynamical simulations - Artale, Maria Celeste (2015)
We explored the role of X-ray binaries composed by a black hole and a massive stellar companion [black hole X-ray binaries (BHXs)] as sources of kinetic feedback by using hydrodynamical cosmological simulations. Following previous results, our BHX model selects metal-poor stars (Z = [0, 10−4]) as possible progenitors. The model that better reproduces observations assumes that an ∼20 per cent fraction of low-metallicity black holes are in binary systems which produces BHXs. These sources are estimated to deposit ∼1052 erg of kinetic energy per event. With these parameters and in the simulated volume, we find that the energy injected by BHXs represents ∼30 per cent of the total energy released by Type II supernova and BHX events at redshift z ∼ 7 and then decreases rapidly as baryons get chemically enriched. Haloes with virial masses smaller than ∼1010 M (or Tvir 105 K) are the most directly affected ones by BHX feedback. These haloes host galaxies with stellar masses in the range 107–108 M. Our results show that BHX feedback is able to keep the interstellar medium warm, without removing a significant gas fraction, in agreement with previous analytical calculations. Consequently, the stellar-to-dark matter mass ratio is better reproduced at high redshift. Our model also predicts a stronger evolution of the number of galaxies as a function of the stellar mass with redshift when BHX feedback is considered. These findings support previous claims that the BHXs could be an effective source of feedback in early stages of galaxy evolution.